Developing Local Education Content Supplementary Textbook Innovation by Referencing to Women in Floating Market - Ismi Rajiani; Harun Joko Prayitno; Sebastian Kot; Norain Ismail; Widya Prihesti Iswarani (Universitas Muhammadiyah Surakarta, 2023)
For local content is required in the Indonesian curriculum, the current study aims at determining local values derived from women struggling in floating markets of South Kalimantan, Indonesia. Five distinctive values were revealed using direct observation and Delphi Techniques: a high tolerance for ambiguity, sustainable innovation, independence, high risk-taking propensity, and external locus of control. Since teachers consist-ently claim that materials centred on events on the island of Java (Java-based approach) dominate social studies instruction, the finding of this study can be used as a model for developing supplementary materi-al based on the real example of locality uniqueness.